Interpretation of DIAL measurements of lower stratospheric ozone in regions with Pinatubo aerosols - Grant, William B.; Browell, Edward V.; Fenn, Marta A.; Butler, Carolyn F.; Brackett, Vincent G.; Veiga, Robert E.; Mayor, Shane D.; Fishman, Jack; Nganga, D.; Minga, A. (1992)
The influence of volcanic aerosols on stratospheric ozone is a topic of current interest, especially with the June 15, 1991 eruption of Mt. Pinatubo in the Philippines. Lidar has been used in the past to provide aerosol profiles which could be compared with ozone profiles measured using ozonesondes to look for coincidences between volcanic aerosols and ozone decreases. The differential absorption lidar (DIAL) technique has the advantages of being able to measure ozone and aerosol profiles simultaneously as well as being able to cover large geographical regions rapidly. While there are problems associated with correcting the ozone profiles for the presence of aerosols, the corrections can be made reliably when the wavelengths are closely spaced and the Bernoulli method is applied. The DIAL measurements considered in this paper are those obtained in the tropical stratosphere in January 1992 during the Airborne Arctic Stratospheric Expedition (AASE-II). The determination of ozone profiles in the presence of Pinatubo aerosols is discussed in a companion paper.